Ship emissions amplify soluble iron in PM2.5 in a typical coastal port in North China - Yiqi Chen; Wei Tan; Yuan Fang; Qi Yuan; Yujue Wang; Weiwei Guan; Minkang Zhi; Xiaohuan Liu; Liang Xu; Jian Zhang; Guochen Wang; Xiaohong Yao; et al. (Environmental Pollution, 2026)

Wollastonite enhances microbial diversity and ecological network stability - Yanzhi Wang; Yongfeng Wang; Ronghua Kang; Chunjie Tian; Guochen Li; Feifei Zhu; Ang Wang; Geshere Abdisa Gurmesa; Chenxia Su; Chang Liu; Dong Liu; Zhi Quan; et al. (Applied Soil Ecology, 2026)

Constructed wetland substrate–mediated stereoselective transformation of metolachlor: Influence of redox conditions and microbial community dynamics - Liangjin Chen; Yucong Zheng; Mawuli Dzakpasu; Qian Yang; Guochen Liu; Liping Zhao; Tianfu Wu; Dongfu Zhang; Xiaochang Wang; Rong Chen (Environmental Research, 2026)

Molecular engineering for synthesizing flocculation /extraction bifunctional polymer and one-way liquid–liquid mass transfer at oil/water interfaces - Guo Liu; Xing Luo; Shengxin Wang; Yulin Shi; Guochen Bai; Heling Guo; Ayyaz Ahmad; Tingting Wei (Desalination, 2026)

Molecular phylogeography and population history of Saccostrea mordax based on mitochondrial DNA - Zeyu Tang; Cui Li; Guochen Zang; Zhenqiang Liu; Zongmei Cui; Haiyan Wang (Journal of Oceanology and Limnology, 2026)

Redox-regulated plastoglobule ABC1K1–ABC1K3 kinase complex controls plastoquinone mobilization for chloroplast photosynthetic adaptation to red light - Mei Yang; Hao Huang; Chao Xu; Xue Han; Guochen Qin; Le Chang; Fang Lin; Xuncheng Wang; Hang He; Xing Wang Deng (Molecular Plant, 2025)

Wollastonite improves soybean yield without toxic trace elements enrichment - Yanzhi Wang; Ji Chen; Guochen Li; Chao Gong; Ang Wang; Ronghua Kang; Feifei Zhu; Jiaoyue Wang; Chang Liu; Dong Liu; Chenxia Su; Quanping Zhang; et al. (Nutrient Cycling in Agroecosystems, 2025)

Origin of granitic pegmatites: Perspectives from elements and Li Hf isotopes, Chakabeishan, northern Tibetan Plateau - Wenli Sun; Zhidan Zhao; Xuanxue Mo; Guochen Dong; Xiaowei Li; Wanming Yuan; Tao Wang; Bingzhang Wang; Tong Pan; Jie Han; Yan Tang; Ningyuan Qi; et al. (Lithos, 2025)

Scalable, durable MOF@PEI-based nanofiber membrane for efficient synergistic removal of Cr(VI) in wastewater - Jun Gao; Ze Mao; Dengbing Wang; Yuan Chen; Hanlei Lin; Jiongsheng Song; Dingsheng Wu; Shen Li; Guochen Bian; Zhenyu Li; Quan Feng (Journal of Environmental Chemical Engineering, 2025)

Organic nitrates in coastal aerosols: Seasonal dynamics, influencing factors, and formation pathways - Mengke Tian; Zhijian Ding; Jia Chen; Juntao Huo; Guochen Wang; Jian Xu; Hao Li; Ziwei Liu; Yunkai Wang; Nan Ye; Xiaofei Qin; Yanfen Lin; et al. (Atmospheric Environment, 2025)

Prenatal genistein exposure in rats affects pubertal onset and serum reproductive hormone levels in male offsprings via the hypothalamic-pituitary-gonadal axis - Jing Zi; Guochen Ma; Yifan Hu; Xinlong Li; Qianqian Cao; Yanliu Li; Xiaoyu Wang; Guo Cheng; Jingyuan Xiong (Food and Chemical Toxicology, 2025)

Smart UAV-assisted blueberry maturity monitoring with Mamba-based computer vision - Fan Zhao; Yinyin He; Jian Song; Jiaqi Wang; Dianhan Xi; Xinlei Shao; Qingyang Wu; Yongying Liu; Yijia Chen; Guochen Zhang; Chenyu Zhang; Yulun Chen; et al. (Precision Agriculture, 2025)
Purpose Precise segmentation of blueberry maturity is critical for optimizing harvestschedules and maintaining product quality. Traditional methods, which rely on manualinspection, are not only labor-intensive but also cost-inefficient. This study presents a novelframework that integrates deep learning-based super-resolution reconstruction (SRR) withsemantic segmentation to provide a fast and accurate solution for maturity assessment. Methods The SRR module enhances image resolution, enabling more detailed feature extraction.Semantic segmentation models—incorporating convolutional neural networks (CNNs),Transformer-based models, and the Mamba-based state space architecture—further improvesegmentation precision. Results Experimental results indicate that the MambaIR modelachieves a structural similarity index measure (SSIM) of 82.26% in SRR tasks, while the Mamba-based segmentation model attains a mean Intersection over Union (mIoU) of 83.15%. Conclusion By uniting SRR and semantic segmentation, our framework not only advances thetechnical accuracy of maturity detection but also holds strong potential for real-time, cost-effective deployment in precision agriculture systems, supporting intelligent decision-making at scale.

A robust black carbon prediction model derived from observational datasets in the Yangtze River Delta region, China - Lian Duan; Pak Lun Fung; Qingyan Fu; Jia Chen; Juntao Huo; Kan Huang; Guochen Wang; Martha Arbayani Zaidan; Zhigang Guo; Tareq Hussein (Environmental Pollution, 2025)

Zircon chemistry of the late cretaceous-eocene granites from Tengchong block: insights into the genesis of host magmas - Zhuanrong Sun; Guochen Dong; Jianheng Guo; Zhongbao Wang (Mineralogy and Petrology, 2025)

Seafloor debris detection using underwater images and deep learning-driven image restoration: A case study from Koh Tao, Thailand - Fan Zhao; Baoxi Huang; Jiaqi Wang; Xinlei Shao; Qingyang Wu; Dianhan Xi; Yongying Liu; Yijia Chen; Guochen Zhang; Zhiyan Ren; Jundong Chen; Katsunori Mizuno (Marine Pollution Bulletin, 2025)

The effect of continental aerosols on cloud-rain transition processes in winter based on aircraft observations - Shuo Wang; Xin Zhang; Dianguo Zhang; Guangzhi Ren; Wenjun Li; Liang Xu; Guochen Wang; Weijun Li (Atmospheric Research, 2025)

Enhanced rock weathering boosts ecosystem multifunctionality via improving microbial networks complexity in a tropical forest plantation - Xing Wang; Guochen Li; Arshad Ali; Camelia Algora; Manuel Delgado-Baquerizo; Daniel S. Goll; Sara Vicca; Tongtong Xu; Boyuan Bi; Qiong Chen; Luxiang Lin; Yunting Fang; et al. (Journal of Environmental Management, 2025)

Investigation of tensile strength and deformation behaviors of basalt fiber-reinforced loess subjected to dry-wet cycles - Zhipeng Wu; Jian Xu; Henghui Fan; Liang Li; Guochen Wang; Songhe Wang (Bulletin of Engineering Geology and the Environment, 2025)

Transient HR enhancement by RAD51-stimulatory compound confers protection on intestinal rather than hematopoietic tissue against irradiation in mice - Zhiyu Lu; Dong Chen; Ning Zhang; Zhiyuan Zheng; Zimo Zhou; Guochen Liu; Jiawei An; Yong Wang; Yongping Su; Wensheng Chen; Fengchao Wang (DNA Repair, 2024)

Multi-process atmospheric particle number size distribution over the Bohai Sea: Insights from cruise and onboard unmanned aerial vehicle observations - Ziwei Liu; Hao Li; Jie Tang; Mian Wang; Haitao Zheng; Tao Luo; Xiaoquan Song; Chengfeng Liu; Guochen Wang; Xiaofei Qin; Jia Chen; Da Lu; et al. (Atmospheric Environment, 2024)

Species composition and distribution of common Crassostrea and Saccostrea oysters along the coast of Hainan Island - Ruijing Lu; Ya Chen; Peizhen Ma; Cui Li; Zhen Zhang; Guochen Zang; Zhenqiang Liu; Haiyan Wang (Journal of Oceanology and Limnology, 2024)

Transpiration and water use sources of poplar (Populus × xiaozhuanica) plantations with 7-years vs. 20-years old in a semiarid sandy region of Northeast China - Lining Song; Jiaojun Zhu; Xin Liu; Jinxin Zhang; Xiao Zheng; Yirong Sun; Guochen Wang; Linyou Lü (Agricultural and Forest Meteorology, 2024)

Enhanced silicate weathering accelerates forest carbon sequestration by stimulating the soil mineral carbon pump - Tongtong Xu; Zuoqiang Yuan; Sara Vicca; Daniel S. Goll; Guochen Li; Luxiang Lin; Hui Chen; Boyuan Bi; Qiong Chen; Chenlu Li; Xing Wang; Chao Wang; et al. (Global Change Biology, 2024)
Enhanced silicate rock weathering (ERW) is an emerging strategy for carbon dioxide removal (CDR) from the atmosphere to mitigate anthropogenic climate change. ERW aims at promoting soil inorganic carbon sequestration by accelerating geochemical weathering processes. Theoretically, ERW may also impact soil organic carbon (SOC), the largest carbon pool in terrestrial ecosystems, but experimental evidence for this is largely lacking. Here, we conducted a 2‐year field experiment in tropical rubber plantations in the southeast of China to evaluate the effects of wollastonite powder additions (0, 0.25, and 0.5 kg m −2 ) on both soil organic and inorganic carbon at 0–10 cm depth. We found that ERW significantly increased the concentration of SOC and HCO 3 − , but the increases in SOC were four and eight times higher than that of HCO 3 − with low‐ and high‐level wollastonite applications. ERW had positive effects on the accrual of organic carbon in mineral‐associated organic matter (MAOM) and macroaggregate fractions, but not on particulate organic matter. Path analysis suggested that ERW increased MAOM mainly by increasing the release of Ca, Si, and Fe, and to a lesser extent by stimulating root growth and microbial‐derived carbon inputs. Our study indicates that ERW with wollastonite can promote SOC sequestration in stable MOAM in surface soils through both the soil mineral carbon pump and microbial carbon pump. These effects may have been larger than the inorganic CDR during our experiment. We argue it is essential to account for the responses of SOC in the assessments of CDR by ERW.

Temporal trend and driving effect of demographic transitions on embedded carbon emissions of Chinese households - Shuo Wang; Wenjin Zhao; Xian’en Wang; Guochen Zheng (Environmental Science and Pollution Research, 2024)

Design and synthesis of low-potential and cycling-stable cobalt dicarboxylate bipyridine complexes for high-voltage aqueous organic redox flow batteries - Bin Liu; Wei Wei; Yu Wang; Manrong Song; Youke Chen; Honglin Chen; Liuping Chen; Qiuxia Dai; Shengxin Yao; Junhui Xu; Guochen Jia; Tianshou Zhao (Science Bulletin, 2024)

Enhanced rock weathering increased soil phosphorus availability and altered root phosphorus‐acquisition strategies - Boyuan Bi; Guochen Li; Daniel S. Goll; Luxiang Lin; Hui Chen; Tongtong Xu; Qiong Chen; Chenlu Li; Xing Wang; Zhanqing Hao; Yunting Fang; Zuoqiang Yuan; et al. (Global Change Biology, 2024)
Enhanced rock weathering (ERW) has been proposed as a measure to enhance the carbon (C)‐sequestration potential and fertility of soils. The effects of this practice on the soil phosphorus (P) pools and the general mechanisms affecting microbial P cycling, as well as plant P uptake are not well understood. Here, the impact of ERW on soil P availability and microbial P cycling functional groups and root P‐acquisition traits were explored through a 2‐year wollastonite field addition experiment in a tropical rubber plantation. The results show that ERW significantly increased soil microbial carbon‐use efficiency and total P concentrations and indirectly increased soil P availability by enhancing organic P mobilization and mineralization of rhizosheath carboxylates and phosphatase, respectively. Also, ERW stimulated the activities of P‐solubilizing ( gcd , ppa and ppx ) and mineralizing enzymes ( phoADN and phnAPHLFXIM ), thus contributing to the inorganic P solubilization and organic P mineralization. Accompanying the increase in soil P availability, the P‐acquisition strategy of the rubber fine roots changed from do‐it‐yourself acquisition by roots to dependence on mycorrhizal collaboration and the release of root exudates. In addition, the direct effects of ERW on root P‐acquisition traits (such as root diameter, specific root length, and mycorrhizal colonization rate) may also be related to changes in the pattern of belowground carbon investments in plants. Our study provides a new insight that ERW increases carbon‐sequestration potential and P availability in tropical forests and profoundly affects belowground plant resource‐use strategies.

Wollastonite powder application increases rice yield and CO2 sequestration in a paddy field in Northeast China - Fangna Wang; Feifei Zhu; Deze Liu; Yuying Qu; Dong Liu; Jin Xie; Ang Wang; Ronghua Kang; Zhi Quan; Yinghua Li; Xin Chen; Guochen Li; et al. (Plant and Soil, 2024)

Circ_0059457 Promotes Proliferation, Metastasis, Sphere Formation and Glycolysis in Breast Cancer Cells by Sponging miR-140-3p to Regulate UBE2C - Li Huang; Guochen Zhang; Lei Han; Xiangdong Bai; Zhibin Xi; Fan Wang; Guohui Han (Biochemical Genetics, 2024)

Apatite chemistry of Late Triassic granitic rocks from Yidun Terrane: Implications for petrogenesis and mineralization - Zhuanrong Sun; Guochen Dong; Jiahui Tang; Jianheng Guo; Zhongbao Wang (Mineralogy and Petrology, 2023)

Atmospheric saccharides over the East China Sea: Assessment of the contribution of sea-land emission and the aging of levoglucosan - Mengxin Fu; Hao Li; Lan Wang; Mengke Tian; Xiaofei Qin; Xuan Zou; Cheng Chen; Guochen Wang; Congrui Deng; Kan Huang (Science of The Total Environment, 2023)

Unveiling the pollution and risk of atmospheric (gaseous and particulate) polycyclic aromatic hydrocarbons (PAHs) in a heavily polluted Chinese city: A multi-site observation research - Tao Wang; Luyao Zhang; Pei Zhang; Guangyuan Yu; Chong Chen; Xiaofei Qin; Guochen Wang; Xiansheng Liu; Rui Li; Liwu Zhang; Zhonghuan Xia (Journal of Cleaner Production, 2023)

Seasonal differences in continental outflows and marine emissions of organic aerosols in the East China Sea: Insight from the variation of saccharides - Hao Li; Lan Wang; Xiaofei Qin; Guochen Wang; Mengxin Fu; Cheng Chen; Jian Xu; Congrui Deng; Kan Huang (Atmospheric Research, 2023)

Dietary factors and gestational diabetes mellitus: An umbrella review - Guochen Ma; Yujie Xu; Haoqi Li; Yaxian Zeng; Xiaoyu Wang; Shufang Shan; Jingyuan Xiong; Guo Cheng (Trends in Food Science & Technology, 2023)

Relationship between light absorption properties of black carbon and aerosol origin at a background coastal site - Haiyan Li; Chengfeng Liu; Hao Li; Guochen Wang; Xiaofei Qin; Jia Chen; Yanfen Lin; Juntao Huo; Qingyan Fu; Yusen Duan; Congrui Deng; Kan Huang (Science of The Total Environment, 2023)

PM2.5-bound polycyclic aromatic hydrocarbons of a megacity in eastern China: Source apportionment and cancer risk assessment - Lian Duan; Huimin Yu; Qiongzhen Wang; Yibo Cao; Guochen Wang; Xueshi Sun; Hao Li; Tian Lin; Zhigang Guo (Science of The Total Environment, 2023)

Design and testing of a mechanized brush-screen cooperative vibration harvester for mudflat-buried shellfish based on the discrete element method - Hangqi Li; Gang Mu; Hanbing Zhang; Hao Wu; Fawei Liu; Zhenyin Sun; Qian Zhang; Yizhou Wang; Yurui Wang; Xiuchen Li; Guochen Zhang (Frontiers in Marine Science, 2023)
Introduction To enhance the application of mechanized harvesting and supplement research on harvesting theory in mudflat-buried shellfish harvesting in China, a brush-screen cooperative mudflat-buried shellfish vibration harvester was designed. Methods The harvester is primarily composed of a crank rocker double-layer vibrating screen, two stage rolling brush, and a conveyor chain. White clams ( Mactra veneriformis ) cultured in mudflats were used as the research objects in this paper, and the mechanics and motion states of the shellfish on the vibrating screen were analyzed. The shellfish harvesting simulation response surface experiments based on the discrete element method (DEM) were conducted to analyze the influence of the main operating parameters on the quantity of shellfish harvested. Results The results revealed that the number of shellfish harvested was significantly influenced ( p < 0.01) by vibrating screen amplitude, first-stage spiral rolling stainless steel brush rotation rate, and harvester travel speed. The optimal combination of key parameters was 1.4 mm, 40 rpm, and 10 m/min, respectively. With these values, the projected shellfish crushing rate was 2.82% and the shellfish harvesting efficiency was 125 pieces/m 2 . The equipment was then manufactured and the shellfish harvesting verification test was performed under the same operating parameters as the simulation. Test results indicated that the harvesting efficiency of the equipment was 114 pieces/m 2 and the shellfish crushing rate was 6.97%. Discussion The shellfish harvesting work could be completed by the equipment effectively and with low loss. The results of this study provide a theoretical reference for a novel mechanized method of harvesting mudflat-buried shellfish.

Seasonal source identification and formation processes of marine particulate water soluble organic nitrogen over an offshore island in the East China Sea - Mengke Tian; Hao Li; Guochen Wang; Mengxin Fu; Xiaofei Qin; Da Lu; Chengfeng Liu; Yucheng Zhu; Xingzhang Luo; Congrui Deng; Sabur F. Abdullaev; Kan Huang (Science of The Total Environment, 2023)

A modeling approach to the efficient evaluation and analysis of water quality risks in cold zone lakes: a case study of Chagan Lake in Northeast China - Fan Wang; Jianmin Bian; Guochen Zheng; Murong Li; Xiaoqing Sun; Chunpeng Zhang (Environmental Science and Pollution Research, 2022)

Transpiration of Pinus sylvestris var. mongolica trees at different positions of sand dunes in a semiarid sandy region of Northeast China - Lining Song; Jiaojun Zhu; Xinjunyan Li; Kai Wang; Guochen Wang; Haihong Sun (Trees, 2022)

An optimal 125-point scheme for 3D frequency-domain scalar wave equation - Lingyun Yang; Guochen Wu; Yunliang Wang; Qingyang Li; Hao Zhang (Acta Geophysica, 2022)

Predicting the near-field strong ground motion based on uncertainties in asperities: an opportunity to reproduce the characteristics of the 1970 Tonghai earthquake (Ms 7.8) - Zongchao Li; Jize Sun; Xueliang Chen; Guochen Wang; Qingfeng Ding (Journal of Seismology, 2021)

Early cretaceous igneous activities in the north flank of the North China Craton: the Shouwangfen complex example - Pengsheng Dong; Guochen Dong; M. Santosh; Zhuanrong Sun; Huawei Li; Shushu Wang; Weiqing Wang (International Geology Review, 2020)

Divergent growth responses to warming and drying climates between native and non-native tree species in Northeast China - Lining Song; Jiaojun Zhu; Jinxin Zhang; Kai Wang; Linyou Lü; Fengbai Wang; Guochen Wang (Trees, 2019)

Triassic ore-bearing and barren porphyries in the Zhongdian Arc of SW China: implications for the subduction of the Palaeo-Tethys Ocean - Peng Wang; Guochen Dong; M. Santosh; Xuefeng Li; Meiling Dong (International Geology Review, 2017)

The accumulation and health risk of heavy metals in vegetables around a zinc smelter in northeastern China - Bo Li; Yanhong Wang; Yong Jiang; Guochen Li; Jiehua Cui; Ying Wang; Hong Zhang; Shicheng Wang; Sheng Xu; Ruzhen Wang (Environmental Science and Pollution Research, 2016)

Zn2+ and mPTP Mediate Endoplasmic Reticulum Stress Inhibition-Induced Cardioprotection Against Myocardial Ischemia/Reperfusion Injury - Guochen Wang; Hongping Huang; Huan Zheng; Yonggui He; Yidong Zhang; Zhelong Xu; Liu Zhang; Jinkun Xi (Biological Trace Element Research, 2016)

The Resistance Analysis of Ureaplasma urealyticum and Mycoplasma hominis in Female Reproductive Tract Specimens - Guangyong Ye; Zhou Jiang; Min Wang; Jiamin Huang; Guochen Jin; Shiming Lu (Cell Biochemistry and Biophysics, 2014)

Identification of SCAR markers linked to or, a gene inducing beta-carotene accumulation in Chinese cabbage - Fenglan Zhang; Guochen Wang; Mei Wang; Xiucun Liu; Xiuyun Zhao; Yangjun Yu; Deshuang Zhang; Shuancang Yu (Euphytica, 2008)